Influence of porosity, degree of hydration, and effects on temperature on compressive strength of OPC paste - Dejeto, Rodrigo V. (Philippine Engineering Journal)
Ordinary Portland cement (OPC) is used worldwide as basic construction material. Studying its physical, chemical and microstructural properties is important. In this study, the influence of porosity, degree of hydration and the effect of temperature on the strength of Japan OPC were evaluated using the water/cement ratio (w/c) of 0.40 and intensive procedures in sample preparation and testing. High early compressive strength development, fast degree of hydration and decreased porosity were observed in 3-day cement cured at 40oC. However, the strength and degree of hydration begun to decline after 28 days of curing period which was nearly comparable to cement cured at room temperature.